Digital Data Management as Indigenous Resurgence in Kahnawà:ke - McMahon, Rob; LaHache, Tim; Whiteduck, Tim (International Indigenous Policy Journal, 2015)
Indigenous peoples are addressing the ongoing impacts of settler colonialism through a variety of expressions of community resurgence. Among these initiatives are those leveraging digital technologies. In the emergent network society, digital infrastructures, and information and communication technologies are powerful tools that can support self-government. In this context, we document the development of digital data management in the Mohawk community of Kahnawà:ke. Data is the digital information generated by a community, encompassing areas like research, education, finance, health, membership, housing, lands, and resources. As self-determining political entities, each First Nation determines how this data is interpreted and used, supported by tools like data management platforms and information-sharing protocols. In this article, we show how local practices regarding the collection, use, and sharing of digital data in Kahnawà:ke provides a clear example of Indigenous resurgence.